2004
DOI: 10.1007/s00468-003-0284-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a severe drought on Quercus ilex radial growth and xylem anatomy

Abstract: We assessed the response of Quercus ilex subsp. ballota to the severe summer drought recorded in 1994 in NE Spain through the study of changes in radial growth and wood anatomy. We selected a coppice stand in the Iberian Peninsula, which is characterized by a Mediterranean climate under continental influence. We measured internode length, tree-ring width, mean and maximum vessel diameter, and vessel density for 1981-1997. The annual predicted hydraulic conductance (K h ) was calculated following Hagen-Poisseui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(47 citation statements)
references
References 75 publications
7
38
2
Order By: Relevance
“…In this study, the overall frequency distribution of vessel was left-skewed, as previously reported for Q. faginea (Villar-Salvador et al 1997, Corcuera et al 2004a, Alla & Camarero 2012, Q. robur and Q. ilex (García-González & Eckstein 2003, Campelo et al 2010, Corcuera et al 2004b). The vessel distribution seems age-related, and the …”
Section: Discussionsupporting
confidence: 78%
“…In this study, the overall frequency distribution of vessel was left-skewed, as previously reported for Q. faginea (Villar-Salvador et al 1997, Corcuera et al 2004a, Alla & Camarero 2012, Q. robur and Q. ilex (García-González & Eckstein 2003, Campelo et al 2010, Corcuera et al 2004b). The vessel distribution seems age-related, and the …”
Section: Discussionsupporting
confidence: 78%
“…Water stress did reduce the number of stomata, presumably in response to drought, consistently with Salisbury & Ross (1985) and Woodward (1987) who showed that the density is controlled by endogenous and environmental factors. Water stress also appeared to reduce vessel size, in agreement with observations by Sass & Eckstein (1995) and Corcuera et al (2004) on other tree species. While vessel sizes remained constant in the outside plot, the smaller diameter vessels observed under imposed drought treatments in the polythene tunnel indicated a plastic response to environmental conditions.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 78%
“…Furthermore, vessel size has been shown to acclimate to the availability of spring and summer precipitation in Quercus robur (Gárcia-González & Eckstein 2003). Similar responses in the Mediterranean region have been found in both the diffuse-porous Q. ilex (Corcuera et al 2004, Campelo et al 2010) and the ring-porous Q. pyrenaica (Corcuera et al 2006). Shake may also be related to shortage of nutrients on the poor soils that commonly support chestnut plantations.…”
Section: Introductionmentioning
confidence: 52%
“…However, fewer studies have attempted to identify the underlying functional problem in "weak" individuals. Most of the studies dealing with the decline of holm oak at individual tree level have focused mainly on characterizing the effects or symptoms of decay in the aerial part of the stools, both at leaf and xylem level (Tognetti et al, 1998;Camarero et al, 2004;Corcuera et al, 2004), sometimes through water exclusion experiments (Limousin et al, 2009;Barbeta et al, 2013;Pérez-Ramos et al, 2013). However, because holm oak is a species with a strong resprouting capacity and as most of the stools have been managed in a coppice system over a long period of time, it would seem reasonable to assume that the cause of decay of some stools may be at least partially explained by factors relating to the root system .…”
Section: Introductionmentioning
confidence: 99%